(untitled) (Open International Journal of Informatics, 2019)
This paper attempts to propose a benchmark for the standard time to complete daily paperwork received at a forwarding company. This research used the define-measure-analyse-improve- control (DMAIC) approach, which was adopted for improving the process capability in an Import Clearance Department. The result from this research found that the import clearance agent required 3 days or more to clear paperwork for duty or tax confirmation. The impact led to delayed shipment delivery, caused by customer dissatisfaction and company loss of trusts amongst customers. It was found that that the number of paperwork received daily was 516, distributed among an average of 15 employees, from January to April 2018. Each employee received an average of 34 paperwork daily. The amount of paperwork received by each employee was at alarming level. The time required to complete paperwork for duty/tax confirmation were 3 days or more for most of the employees, which stood at 62%. Therefore, based on the results of the findings, the proposed benchmark of the standard time for paperwork clearance should not be more than 1 day to allow for same day delivery to the customers, as per the commitment promised by the company.